Penerapan Model Pembelajaran Problem Based Learning pada mata Pelajaran Dasar Listrik dan Elektronika - Aretnaldi Putra; Fivia Eliza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research aims to see the impact of applying the Problem-Based Learning model on student learning outcomes in the basic subjects of electricity and electronics in class X TTL2 SMK N 2 Sungai Penuh, a total of 30 people. The achievement of student learning outcomes is still disappointing with many students who have not reached the KKM. the low learning outcomes of students caused by the learning process which is centered on educators and the lack of activeness of students. This makes some students be passive, and noisy, play on mobile phones, talk to their friends, and not listen clearly to the material presented. This study used quantitative research using the pre-experimental method with the one-group pretest-posttest design type. The results of the pretest-posttest data obtained were analyzed using an effect size with a value of 0.88 in the large category. Based on the results of the study, it was found that the learning outcomes of students experienced an increase after the application of the problem-based learning model.